Transdisciplinary embodied education in elementary school: a real integrative approach for the science, technology, engineering, arts, and mathematics teaching - Almarcha, Maricarmen; Vázquez, Pablo; Hristovski, Robert; Balagué, Natàlia (Frontiers in Education, 2023)
Connecting academic disciplines and integrating knowledge is gaining popularity in elementary school. The relevant question is, how the targeted integration could be achieved? This research aimed to a) evaluate the potential of teaching and learning Dynamic Systems Theory (DST) and Statistical Physics (ST) general concepts through embodied experiences in elementary school and, based on it b) enable a far transfer analogical reasoning within and between different academic subjects. Forty-eight elementary school students, aged 10,2 ±0,82 y.o., followed an 8-week, 2-hour/week intervention. The learning protocol contained a concreteness fading sequence of phases and consisted of four steps: a) embodied experience, b) reflective observation, c) abstract conceptualization of DST/ST concepts, and d) transfer of the DST/SP concepts to physical, sociological, biological and ecological phenomena. A validated questionnaire and an interview evaluated students’ knowledge and analogical reasoning. The Wilcoxon Signed Ranks Test showed a general positive effect of the intervention on the understanding of DSP/SP concepts and on the far transfer competencies of students (Z = -5.98; p < 0.0001). There was no association between the previous and newly acquired competencies (Spearman’s ρ = 0.112; p = 0.441). The qualitative results showed that, in general, the suggested embodied learning protocol supports the acquisition of DST/SP general concepts and the far transfer competencies. However, students of this age are possibly highly sensitive to the balance of the focus between the embodied phases and the conceptualization/transfer phases of the learning protocol. The study points to the potential of learning the general DST/SP for elementary school students' integrative and far transfer competencies. The DST/SP concept-based transdisciplinary embodied education may offer a truly integrative approach to STEAM teaching.